Cueva de El Toro (Antequera, Malaga-Spain): a Neolithic stockbreeding community in the Andalusian region, between the 6th and 3th millennia BC - María Dolores Cámalich; R. Buxó; E. Chávez; J. C. Echallier; Pedro Gonzáles; Antonio Goñi; M. Mañosa; T. Orozco; M. A. Paz; M. O. Rodríguez; A. Rodríguez; M. Tusell; et al. (Documenta Praehistorica, 2004)
The occupation evidence shown by the cave El Toro, is that of a unique stockbreeding community in the Andalusian region. The calibrated dates for this occupation period go from the second quarter of the sixth millennium up to the second millennium BP. There is also evidence of occasional occupation throughout later millennia up to the Hispano-Muslim period. The nature of thisoccupation is determined by the close link between the cave and the community which occupied it, both continuously and periodically. Throughout the occupation levels, the community's skillful control of technical processesand its remarkable knowledge on how to transform local primary resources, have shown that this community reached a high level of technological development. However, its main economic activity was related to agricultural and farming exploitation, particularly to stockbreeding.